2010
DOI: 10.1007/s00595-010-4388-8
|View full text |Cite
|
Sign up to set email alerts
|

The effect of traditional Japanese medicine (Kampo) on gastrointestinal function

Abstract: Traditional Japanese medicine (Kampo) is used to treat various disorders of the gastrointestinal tract in Japan, where it is fully integrated into the modern healthcare system. Recently, scientific research on herbal medicine in Japan has been reported in English journals. The objective of the current review is to introduce two traditional Japanese medicines and to provide evidenced-based information regarding their use. Daikenchuto, which consists of three different herbs, is the most frequently prescribed tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 44 publications
0
27
0
Order By: Relevance
“…An infusion of ghrelin increases circulating plasma growth hormone in rodents and humans [7][8][9]. However, other actions of ghrelin have emerged, such as a role in glucose metabolism and insulin release [10,11], cardiovascular actions [12,13], and an effect on food intake and control of energy balance [14][15][16]. Intravenous ghrelin injection has been found to accelerate gastric emptying after a meal and improve symptoms in dyspeptic humans [17].…”
Section: Introductionmentioning
confidence: 98%
“…An infusion of ghrelin increases circulating plasma growth hormone in rodents and humans [7][8][9]. However, other actions of ghrelin have emerged, such as a role in glucose metabolism and insulin release [10,11], cardiovascular actions [12,13], and an effect on food intake and control of energy balance [14][15][16]. Intravenous ghrelin injection has been found to accelerate gastric emptying after a meal and improve symptoms in dyspeptic humans [17].…”
Section: Introductionmentioning
confidence: 98%
“…Since 1986, when the prescription of DKT was included in the national health insurance cover by the Japanese government, DKT has been widely administered to accelerate the recovery of GI function after abdominal surgery and postoperative ileus. In a study of upper GI tract motility, Mochiki et al [34] found that DKT induced phasic contractions in the pylorus, duodenum, and jejunum in conscious dogs. DKT also improved intestinal motility in patients undergoing total gastrectomy with jejunal pouch interposition [35].…”
Section: Discussionmentioning
confidence: 98%
“…They are intended not only to help recover the natural balance of the human body, but also treat the body's impairments, such as indigestion and fatigue 4) . Based on this concept, several kinds of Kampo formula have been widely used for palliative care including cancer associated symptoms and adverse effect of chemotherapy in Japan 5) .…”
Section: Discussionmentioning
confidence: 99%